2007
DOI: 10.1183/09031936.00015506
|View full text |Cite
|
Sign up to set email alerts
|

Changes in HRCT findings in patients with respiratory bronchiolitis-associated interstitial lung disease after smoking cessation

Abstract: High-resolution computed tomography (HRCT) findings in patients with respiratory bronchiolitis-associated interstitial lung disease (RB-ILD) are varied and nonspecific. There is no known report of changes in HRCT findings and respiratory function test results for RB-ILD patients following the cessation of smoking.Five patients with RB-ILD, confirmed by surgical lung biopsy, were retrospectively studied. Each stopped cigarette smoking and did not receive corticosteroid therapy after diagnosis. The clinical symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 30 publications
1
23
1
1
Order By: Relevance
“…Desquamative interstitial pneumonia is a less common entity than respiratory bronchiolitis interstitial lung disease. Previous studies (27,28) have suggested that the CT findings of respiratory bronchiolitis interstitial lung disease are at least partially reversible, which would account for the fact that GGO improved at follow-up in 41% (13 of 32) of participants in our study.…”
Section: Discussionsupporting
confidence: 51%
“…Desquamative interstitial pneumonia is a less common entity than respiratory bronchiolitis interstitial lung disease. Previous studies (27,28) have suggested that the CT findings of respiratory bronchiolitis interstitial lung disease are at least partially reversible, which would account for the fact that GGO improved at follow-up in 41% (13 of 32) of participants in our study.…”
Section: Discussionsupporting
confidence: 51%
“…24 Another study found that centrilobular nodules and ground-glass opacifi cation detected on HRCT scan can be improved by smoking cessation. 25 However, the present study demonstrates that smok ing cessation causes a decrease in the number of micronodules, with no signifi cant changes in ground-glass opacifi cation. Hence, the association of micronodules, ground-glass opacifi cation, and emphysema remains controversial.…”
Section: )contrasting
confidence: 55%
“…BAL findings in RB-ILD patients usually do not differ from those seen in otherwise normal healthy smokers and include an increased total number of cells with a normal cellular differential analysis [[13]] or an increase in the percentage of macrophages [[15]]. These alveolar macrophages contain brownish, golden, or black tobacco pigment inclusions In the absence of these cells, an alternative diagnosis should be considered.…”
Section: Diagnostic Methods and Criteriamentioning
confidence: 99%
“…Additionally, there have been several other reports focused mainly on the differential diagnosis of RB-ILD based on radiological findings [[9]] and their correlation with clinical and physiological findings [[14]], or on follow-up after smoking cessation [[14],[15]].…”
Section: Definitionmentioning
confidence: 99%